Servicescape Sebagai Anteseden Pada Kepuasan Konsumen (Studi Kasus di Gerai Yogyatourium PT. Aseli Dagadu Djokdja Tahun 2019) (GEMA EKONOMI, 2023)
Every consumer who comes to a store or service place will want to get the best service as expected and the service environment is the first aspect that consumers will feel. PT. Aseli Dagadu Djokdja has the largest outlet named Yogyatourium (Yogya Tourism Laboratourium), in this case Dagadu must be able to present a service environment that can make consumers feel satisfied considering that Dagadu is a creative industry company that has been established for quite a long time and has achieved many achievements. The purpose of this study is to determine whether there is a positive influence of the service environment dimension (servicescape) on customer satisfaction at Yogyatourium outlets. The method used in this study is nonparametric statistical analysis to test hypotheses. The sample data of this study was taken by non-probability sampling techniques using incidental and purposive sampling techniques. This means that anyone who visits the Yogyatourium outlet and coincidentally meets the researcher and is considered to fit the predetermined criteria can become a research respondent. The population in this study is all consumers of PT. Aseli Dagadu Djogdja who visited Dagadu Yogyatourium outlet, while the target sample determined was 60 samples. This study uses CFA as a validity test with alpha 0.5 and is declared valid if it has a loading factor value of > 0.5 and the indicator forms one component. Research reliability tests use Cronbach's alpha formula and are declared reliable if they have a reliability coefficient of ≥ 0.6. The results of the analysis in this study state that all variables in the service environment dimension (servicescape) have a positive and significant influence on customer satisfaction. This means that if the better the quality of the servicescape dimension formed, the higher the level of customer satisfaction at Yogyatourium outlets. This research is expected to be useful for readers and for companies to always improve the quality of their service environment.